The transport geography of electric and autonomous vehicles in road freight networks. (October 2019) - Monios, Jason; Bergqvist, Rickard
Abstract: The purpose of this paper is to elaborate the transport geography of electric and autonomous vehicles for road freight transport and establish a research agenda by identifying many unresolved issues already beginning to emerge. While regulatory approval for full coverage on all roads remains some years away, autonomous vehicles are already operating intermodal-style main hauls on major highways, interchanging at highway junctions with the first and last mile performed by regular trucks. Meanwhile, electric trucks capable of medium distances on a single charge are now entering the market. The two technologies of electric propulsion and autonomy are mutually reinforcing, particularly from the network perspective, and purpose-built electric autonomous vehicles (EAVs) are starting to enter commercial service. This paper utilises an analytical framework of intermodal transport to map against the emerging geography of EAVs and determine how our knowledge of the features, challenges, business models and policy implications of intermodal transport can help decision makers plan for a better development of the emerging EAV network. The paper provides recommendations for policymakers dealing with arising challenges and identifies a list of research questions regarding this rapidly evolving new form of transport.